Developing a School Children's Feeding Menu (PMTAS) Based on Local Culture: as an Effort to Prevent Stunting - Fitria Budi Utami; Maya Lestari; Rahmat Saputra; Parmiyatun; Dea Solliana (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Stunting is one of the chronic nutritional problems that inhibits physical growth and cognitive development of children. This study aims to develop a local culture-based Supplementary Food for School Children (PMTAS) menu as an effort to prevent stunting in Early Childhood Education (PAUD) institutions. The method used is Research and Development (R n D) with ADDIE Action model analysis (Analyze, Design, Develop, Implement, Evaluate) which involves needs analysis, menu design, product development, implementation in schools, and evaluation of effectiveness. The results of this study have important implications in the context of stunting prevention, but also in the development of national nutrition and education policies. These findings underline that school-based interventions with a local food-based approach can be used as a model to be applied in various regions in Indonesia. However, adaptation is needed in implementation in areas with different socio-economic and cultural conditions. By focusing on local food, this approach opens up opportunities to create new theories about the role of local culture in food acceptance and its effects on improving children's nutritional status. As an additional contribution to the literature, this study suggests that the role of local culture in food acceptance by children be the focus for theory development. In addition, the role of school-based interventions as a key factor in preventing stunting needs to be explored further, including by considering how parental involvement can be strengthened through school programs.